Global relevance of Aire binding to hypomethylated lysine-4 of histone-3 - Koh, Andrew S. (National Academy of Sciences, 2010)
Aire promotes the ectopic expression of a repertoire of peripheral-tissue antigens (PTAs) in thymic medullary epithelial cells (MECs) to mediate deletional tolerance and thereby prevent autoimmunity. Binding of hypomethylated histone 3 (H3)-tails by Aire's plant homeodomain (PHD) finger is essential for Aire function in cultured cell models, prompting speculation that Aire-PHD:H3-tail interactions underlie targeting of Aire to weakly transcribed loci. To evaluate the role of Aire's PHD finger in MECs on a global scale in vivo, we complemented Aire-deficient mice with a mutant of Aire that inhibits its binding to hypomethylated H3K4 residues. Although the range of Aire-targeted genes was largely unaffected in these mice, the D299A mutation caused a global dampening of Aire's transcriptional impact, resulting in an autoimmune disease similar in profile to that of their Aire-deficient counterparts. To test whether a low H3K4 methylation state is sufficient for Aire targeting, we overexpressed an H3K4-specific demethylase in an Aire-dependent cultured cell system, and determined its capacity to extend Aire's transcriptional footprint. The range and magnitude of Aire-regulated genes was largely unaffected, the only genes additionally induced by Aire in this context being those already accessed for repression. In short, Aire's H3-binding module is necessary for Aire-mediated regulation of gene expression and central tolerance induction, but this influence is unlikely to reflect a targeting mechanism solely based on the recognition of hypomethylated H3K4 residues.